C. elegans and mutants with chronic nicotine exposure as a novel model of cancer phenotype. Issue 1 (2nd January 2016) - Kanteti, Rajani; Dhanasingh, Immanuel; El-Hashani, Essam; Riehm, Jacob J.; Stricker, Thomas; Nagy, Stanislav; Zaborin, Alexander; Zaborina, Olga; Biron, David; Alverdy, John C.; Im, Hae Kyung; Siddiqui, Shahid; et al.
ABSTRACT: We previously investigated MET and its oncogenic mutants relevant to lung cancer in C. elegans . The inactive orthlogues of the receptor tyrosine kinase Eph and MET, namely vab-1 and RB2088 respectively, the temperature sensitive constitutively active form of KRAS, SD551 ( let-60 ; GA89) and the inactive c-CBL equivalent mutants in sli-1 (PS2728, PS1258, and MT13032) when subjected to chronic exposure of nicotine resulted in a significant loss in egg-laying capacity and fertility. While the vab-1 mutant revealed increased circular motion in response to nicotine, the other mutant strains failed to show any effect. Overall locomotion speed increased with increasing nicotine concentration in all tested mutant strains except in the vab-1 mutants. Moreover, chronic nicotine exposure, in general, upregulated kinases and phosphatases. Taken together, these studies provide evidence in support of C. elegans as initial in vivo model to study nicotine and its effects on oncogenic mutations identified in humans.